The Effect of Media Sports Immersion on Smart Phone Users’ Loyalty and Sports Activities - Ik Kim, Nam; Mun Park, Sun (International Journal of Engineering and Technology, 2018)
Modern society is an information society through media, which has a great effect on human behavior, and this social flow also has a great influence on people’s sports activities. In other words, people can acquire information about sports that they want anywhere and anytime, can express their opinions, and can form groups with people who have same interest due to the development of wireless internet and smart phones. In addition, the immersion in media sports is influential as a major factor of sports activities. The immersion on the internet is defined as an important criterion of consumers’ spontaneous interest and as what includes individuals’ pleasure, mental stimulation and awareness of interest. The immersion in media sports is connected to loyalty. The loyalty, which is a factor that affects the decision of human behaviors, means favorable attitudinal and mental attachment. It means the loyalty is preceded until sports activities are performed through media sports. Therefore, this study is intended to reveal the effects of media immersion by media sports involving experiences on sports participation. This study is intended to reveal the effects of media immersion by media sports involving experiences on sports participation. For this study, total 300 participants in their 20s 30s including 150 males and 150 females who experienced media sports using smart phones were selected with the convenience sampling method. Prior to the survey, their media sports involving experiences using smart phones were confirmed. For the questionnaire completion method, self-administration method was used. For analysis of data, the data with answers of questionaries completed were collected, valid samples are coded according to the coding manual with double entry and no entry excluded, the coded data were entered into computer individually, and then frequency analysis, Exploratory Factor Analysis, Reliability Analysis and Multiple Regression Analysis were done with the use of SPSS Windows 18.0 Version statistical program. The results of the study are as follows. First, the immersion of media sports has a partial effect on sports loyalty. Second, the immersion of media sports has a partial effect on sports activities. Third, the high sports loyalty has a partial effect on sports activities. Â Â